Reversible decreased ovarian reserve after conservative ovarian surgery for benign lesion other than endometrioma – case report - Abdelazim, Ibrahim; Zhurabekova, Gulmira (Menopause Review/Przegląd Menopauzalny, 2020)
A 36-year-old woman presented with abdominal pain and diagnosed provisionally as complicated ovarian cyst. The trans-vaginal ultrasound (TVS) done for the studied woman showed, well-defined solid mass, measuring 10 × 8 cm related to the anterior uterine wall most probably subserous uterine leiomyoma or ovarian fibroma. The TVS finding of left solid mass was confirmed by the magnetic resonance imaging (MRI). At laparotomy, the solid mass was originating from the left ovary and the right ovary and uterus were completely normal. The left ovarian mass excised (confirmed as ovarian fibroma by histological examination), and more than half of the left ovary was preserved during surgery. The pre-operative ovarian reserve hormones, anti-Müllerian hormone (AMH), follicle stimulating hormone (FSH), and luteinizing hormone (LH) were completely normal. Post-operative follow-up of the studied woman showed regular menstrual rhythm and duration, elevated FSH and LH for one year after surgery and both the FSH and LH returned to normal levels at the end of the first post-operative year. This report represents the finding of reversible decrease ovarian reserve (RDOR) after conservative ovarian surgery for benign lesion other than endometrioma to minimise normal ovarian tissue damage during surgery as much as possible and to counsel women at risk of DOR that any ovarian surgery may be associated with further decrease in the ovarian reserve and reproductive ability.